Telaah Relevansi Materi Pendidikan Agama Islam Kelas IX Semester I pada Kurikulum Merdeka - Hapsari, Aprilia Putri; Saputra, Wendi (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2025)
This study aims to examine the relevance of Islamic Religious Education (PAI) subject matter for Grade IX, first semester, within the Merdeka Curriculum, particularly in Phase D. The background of this research lies in the need for a critical evaluation of PAI materials to align with students’ developmental needs, while addressing a gap in previous studies that tended to focus on general curriculum design without specifically analysing PAI content at the junior secondary level. This research employs a qualitative approach with a library research method. Primary data sources include official documents from the Ministry of Education, Culture, Research, and Technology, such as the Guidelines for the Implementation of the Merdeka Curriculum (2022) and the Teacher’s Handbook for PAI Grade IX. Secondary data consist of scholarly articles and academic works related to curriculum and Islamic Religious Education. Data were analysed through three stages: classification, categorization, and content analysis to identify the alignment between subject matter and students’ contextual needs. The findings reveal that the PAI materials for Grade IX, first semester, demonstrate strong relevance to students’ cognitive, affective, and social development, as well as support character-building in line with the Profil Pelajar Pancasila. However, at the implementation level, several challenges remain, particularly limited instructional time, teachers’ readiness to adapt the materials, and the integration with cross-disciplinary learning. The study recommends strengthening teachers’ capacity through professional development programs focused on the Merdeka Curriculum, utilizing digital learning media, and conducting continuous evaluations at both the school and national levels. These findings are expected to provide practical contributions for teachers, schools, and policymakers in optimizing the implementation of the Merdeka Curriculum in Islamic Religious Education.